2009
DOI: 10.1073/pnas.0910218106
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal prostaglandin E synthase 1 determines tumor growth in vivo of prostate and lung cancer cells

Abstract: There is strong evidence for a role of prostaglandin E2 (PGE2) in cancer cell proliferation and tumor development. In PGE 2 biosynthesis, cyclooxygenases (COX-1/COX-2) convert arachidonic acid to PGH2, which can be isomerized to PGE2 by microsomal PGE-synthase-1 (MPGES-1). The human prostate cancer cell line DU145 expressed high amounts of MPGES-1 in a constitutive manner. MPGES-1 expression also was detectable in human prostate cancer tissues, where it appeared more abundant compared with benign hyperplasia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 29 publications
2
73
1
2
Order By: Relevance
“…Considering that tumor cells release several cytokines and growth factors that are capable of inducing mPGES-1, such as interleukin-1b, tumor necrosis factor-a and vascular endothelial growth factor (Caso´s et al, 2011), some of these factors secreted from tumor cells may be involved in the induction of mPGES-1 in adjacent MFs. The role of cancer cell-associated mPGES-1 in tumor growth has been demonstrated in studies employing knockdown of mPGES-1 in several tumor cell lines, where its knockdown in LLC cells, the human prostate cancer cell line DU145 and the nonsmall-cell lung cancer cell line A549 reduced their growth in vitro and/or in vivo (when transplanted into mice) (Hanaka et al, 2009;Kamei et al, 2010). We recently found that, in addition to cancer cell-associated mPGES-1, host stromal cell-associated mPGES-1 contributes to tumor growth, in which LLC tumors grafted subcutaneously into mPGES-1 KO mice grew more slowly than did those grafted into WT mice, due at least in part to reduced angiogenesis .…”
Section: Mpges-1 Promotes Colon Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that tumor cells release several cytokines and growth factors that are capable of inducing mPGES-1, such as interleukin-1b, tumor necrosis factor-a and vascular endothelial growth factor (Caso´s et al, 2011), some of these factors secreted from tumor cells may be involved in the induction of mPGES-1 in adjacent MFs. The role of cancer cell-associated mPGES-1 in tumor growth has been demonstrated in studies employing knockdown of mPGES-1 in several tumor cell lines, where its knockdown in LLC cells, the human prostate cancer cell line DU145 and the nonsmall-cell lung cancer cell line A549 reduced their growth in vitro and/or in vivo (when transplanted into mice) (Hanaka et al, 2009;Kamei et al, 2010). We recently found that, in addition to cancer cell-associated mPGES-1, host stromal cell-associated mPGES-1 contributes to tumor growth, in which LLC tumors grafted subcutaneously into mPGES-1 KO mice grew more slowly than did those grafted into WT mice, due at least in part to reduced angiogenesis .…”
Section: Mpges-1 Promotes Colon Carcinogenesismentioning
confidence: 99%
“…Transgenic mice overexpressing both COX-2 and mPGES-1 developed metaplasia, hyperplasia and tumorous growth in the glandular stomach with heavy macrophage (MF) infiltration (Oshima et al, 2004(Oshima et al, , 2005. Furthermore, cell proliferation and invasive activity in vitro and xenograft formation in vivo were reduced by mPGES-1 knockdown and conversely enhanced by mPGES-1 overexpression in lung and prostate cancer cells (Hanaka et al, 2009;Kamei et al, 2010). To better evaluate the efficacy of mPGES-1 inhibition in relieving symptoms of cancer, we herein examined the effect of mPGES-1 deficiency on chemical carcinogen-induced carcinogenesis and found that the absence of mPGES-1 reduces the size and number of colorectal polyps.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the expression of mPGES1 is elevated in a number of human cancers, including breast cancer (13). Knockdown of mPGES1 in both the DU145 prostate cancer cell line and the A549 non-small cell lung cancer cell line inhibits xenograft tumor growth in nude mice (14). mPges1 knockout mice likewise exhibit a significant reduction in both the number and size of intestinal tumors induced by an Apc mutant (15).…”
mentioning
confidence: 99%
“…Cheng et al (2006) has reported that mPGES-1 inhibitor could block PGE2 and make therapeutic effects in many diseases instead of nonsteroidal anti-inflammatory drugs (NSAIDs), meanwhile, no obvious side effects were observed. Recently, Hanaka et al (2009) has focused on the role of mPGES-1 in PCa. He found that mPGES-1 over-expressed in both PCa tissues and human PCa cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting that mPGES-1 is of importance for malignant transformation and progression. Hanaka has demonstrated that there also was a significant high expression of mPGES-1 in PCa cells and high expression of mPGES-1 can promote growth and survival in the cancer cells (Hanaka et al, 2009). These results implied us that inhibition of mPGES-1 is a therapeutic option for cancers that express this enzyme.…”
Section: Introductionmentioning
confidence: 92%